Cellular Uptake Behaviors of Rigidity-Tunable Dendrimers - Hui Liu; Jingjing Wang; Wenchao Li; Jie Hu; Min Wang; Yuejun Kang (MDPI AG, 2018)
Understanding of the interaction between cells and nanoparticles (NPs) is critical. Despite numerous attempts to understand the effect of several parameters of NPs on their cellular uptake behaviors, such as size, shape, surface chemistry, etc., limited information is available regarding NP rigidity. Herein, we investigate the effect of rigidity on cellular uptake behaviors of NPs, using generation 5 poly(amidoamine) dendrimer as a model. By harnessing the abundant inner cavity, their rigidity could be effectively regulated by forming size-tunable gold NPs. The NPs thus formed were well characterized and displayed similar hydrodynamic size, surface potential, fluorescence intensity, and distinct rigidity (owing to differences in the size of the Au core). Flow cytometry analysis revealed a positive correlation between NP rigidity and cellular uptake of NPs. Confocal microscopic evaluation revealed that the entrapped gold NPs may affect the intracellular localization of the internalized dendrimers. The present findings can potentially guide the preparation of suitable NPs for biomedical applications.